2018
DOI: 10.1016/j.celrep.2018.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Limits Tumor Response to VEGFA Inhibition

Abstract: Resistance to antiangiogenic drugs limits their applicability in cancer therapy. Here, we show that revascularization and progression of pancreatic neuroendocrine tumors (PNETs) under extended vascular-endothelial growth factor A (VEGFA) blockade are dependent on periostin (POSTN), a matricellular protein expressed by stromal cells. Genetic deletion of Postn in RIP1-Tag2 mice blunted tumor rebounds of M2-like macrophages and αSMA stromal cells in response to prolonged VEGFA inhibition and suppressed PNET revas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Interestingly, previous reports have indicated that elevated ADAMTS6 expression could suppress tumor progression and serve as a prognostic marker in human cancer, whereas the depletion of ADAMTS6 stimulated cell migration and tumorigenesis (14). Consistently, we also found that knockdown of AGR2 suppressed VEGFA mRNA expression, but knockdown of ADAMTS6 enhanced VEGFA mRNA expression, which is highly related to chemotherapy resistance (53,54), suggesting that AGR2 directly affects the expression of VEGFA, while ADAMTS6 might affect VEGF expression through AGR2 in drug resistance of mutant NSCLC cells. Finally, we further determined the effects of YD on this ADAMTS6-AGR2 -VEGFA axis and found that YD could upregulate ADAMTS6 and downregulate AGR2 expression leading to suppressed VEGFA expression in NSCLC cells.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, previous reports have indicated that elevated ADAMTS6 expression could suppress tumor progression and serve as a prognostic marker in human cancer, whereas the depletion of ADAMTS6 stimulated cell migration and tumorigenesis (14). Consistently, we also found that knockdown of AGR2 suppressed VEGFA mRNA expression, but knockdown of ADAMTS6 enhanced VEGFA mRNA expression, which is highly related to chemotherapy resistance (53,54), suggesting that AGR2 directly affects the expression of VEGFA, while ADAMTS6 might affect VEGF expression through AGR2 in drug resistance of mutant NSCLC cells. Finally, we further determined the effects of YD on this ADAMTS6-AGR2 -VEGFA axis and found that YD could upregulate ADAMTS6 and downregulate AGR2 expression leading to suppressed VEGFA expression in NSCLC cells.…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, the genetic overexpression of Csf1 in the mammary epithelium of MMTV-PyMT mice results in the premature accumulation of macrophages around hyperplastic lesions and adenomas and accelerates both the development of an angiogenic vasculature and tumor progression [545]. These findings are consistent with results obtained using a macrophage-depleting CSF1 receptor (CSF1R) inhibitor [546] and agree with studies in other mouse tumor models, such as RIP1-Tag2 transgenic mice [547]. …”
Section: The Mmtv-pymt Breast Cancer Modelsupporting
confidence: 79%
“…POSTN (periostin; osteoblast‐specific factor 2) encodes a 90‐kDa secreted extracellular matrix protein belonging to the fasciclin family, which has been widely studied in embryogenesis, tumorigenesis, inflammatory diseases, and atherosclerosis . Induced by TGF‐b, IL‐4, and IL‐13, the POSTN gene can modulate the expression of several hub genes such as TGF‐band chemokines and regulate cellular behavior including cell proliferation, epithelial‐mesenchymal transition, and cell migration through interaction with several integrin receptors . High expression of POSTN was mainly observed in early embryonic tissues, adult periosteum, and periodontal ligament .…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Induced by TGF-b, IL-4, and IL-13, the POSTN gene can modulate the expression of several hub genes such as TGF-band chemokines and regulate cellular behavior including cell proliferation, epithelial-mesenchymal transition, and cell migration through interaction with several integrin receptors. 37,39 High expression of POSTN was mainly observed in early embryonic tissues, adult periosteum, and periodontal ligament. 40,41 The abnormal expression of POSTN in stromal cells was associated with an invasive and proliferative phenotype.…”
Section: Discussionmentioning
confidence: 99%